Positive psychology research within the workplace in Namibia: findings and prospects for the future (Namibian Journal for Research, Science and Technology, 2024)
The field of psychology has been criticised for being overly focused on pathology and less focused on the positive aspects of human functioning. Positive psychology research assesses what is going well and seeks to identify ways to learn from these phenomena in order to enhance positive functioning among human beings. Using a desk-based review, this study discusses research related to positive psychology conducted in Namibia within the world of work. The study focused on research published between 2009 and 2019 across different industries, including education, health and social services, government institutions, the service industry, and the mining sector. The recommendations include enhancing positive human qualities, identifying factors that work against positive functioning, improving the working environment, promoting healthy leadership styles, and developing the overall well-being of organisations. This study aims to consolidate existing research within the Namibian context, take stock of current knowledge, and guide future approaches and areas of focus within the field of positive psychology. There is limited research in the field of positive psychology, and even less within the Namibian context. This study therefore aims to help reduce this knowledge gap within the field of psychology.
Keywords: Positive psychology; Well-being; Workplace flourishing; Positive organisational behaviour